2021
DOI: 10.1097/ju.0000000000001901
|View full text |Cite
|
Sign up to set email alerts
|

The Current Evidence for Factors that Influence Treatment Decision Making in Localized Kidney Cancer: A Mixed Methods Systematic Review

Abstract: Introduction: With a growing number of treatment options for localised kidney cancer, patients and health care professionals have both the opportunity and the burden of selecting the most suitable management option. This mixed method systematic review aims to understand the barriers and facilitators of the treatment decision-making process in localised kidney cancer. Methods: We searched PubMed, Embase, and Cochrane Central databases between 1st of January 2004 and 23rd of April 2020 using the JBI Manual for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
(338 reference statements)
1
10
0
Order By: Relevance
“…Another possible reason may lie in the fact that younger patients tend to receive more cost‐intensive care, according to an analysis of the French National Hospital Database from 2008 to 2013 24 . A similar trend was reported in a recent systematic review that suggested that younger patients are more likely to elect expensive surgical procedures (e.g., open or partial nephrectomy) rather than ablation or active surveillance 25 . All of these trends could contribute to faster expenditure growth among young patients given the higher incidence rates and more intensive medical services.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Another possible reason may lie in the fact that younger patients tend to receive more cost‐intensive care, according to an analysis of the French National Hospital Database from 2008 to 2013 24 . A similar trend was reported in a recent systematic review that suggested that younger patients are more likely to elect expensive surgical procedures (e.g., open or partial nephrectomy) rather than ablation or active surveillance 25 . All of these trends could contribute to faster expenditure growth among young patients given the higher incidence rates and more intensive medical services.…”
Section: Discussionsupporting
confidence: 57%
“…24 A similar trend was reported in a recent systematic review that suggested that younger patients are more likely to elect expensive surgical procedures (e.g., open or partial nephrectomy) rather than ablation or active surveillance. 25 All of these trends could contribute to faster expenditure growth among young patients given the higher incidence rates and more intensive medical services. Moreover, our data demonstrated that service utilization did not have as much impact on reduced health expenditures in younger age groups as in older age groups (Table 1), which implies that there still may be room for improvement in service utilization for younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, surgery has been the standard of care for localised renal cancer, but international guidelines have more recently proposed ablative treatments and active surveillance as alternative options [5] , [6] . Currently, oncological outcomes across treatments are similar and treatment decision-making is multifactorial [7] .…”
Section: Introductionmentioning
confidence: 99%
“…COS in urology are needed because inconsistencies and variability cause not only frustration but also potentially problematic conclusions [9] . This issue is also clearly apparent for localised renal cancer, and ultimately results in barriers for the multifactorial process of decision-making [7] .…”
Section: Introductionmentioning
confidence: 99%
“…2 In general, the decision process leading to the treatment of a renal tumor is multifactorial and multifaceted. 3 Accurate patient selection and counseling remain key to making the best “tailored” choice on a case-by-case basis. In referring centers managing renal masses, all these options should be available in the armamentarium of the treating physician.…”
mentioning
confidence: 99%